Neurotransmitter signaling in the pathophysiology of microglia - Domercq, Maria; Vazquez, Nuria; Matute, Carlos (Frontiers in Cellular Neuroscience, 2013)
Microglial cells are the resident macrophages in the central nervous system. In the resting state, microglia are highly dynamic and control the environment by rapidly extending and retracting motile processes. Microglia are closely associated with astrocytes and neurons, particularly at the synapses, and more recent data indicate that neurotransmission plays a role in regulating the morphology and function of "resting" microglia, as they are endowed with receptors for most known neurotransmitters. In particular, microglia express receptors for ATP and glutamate, which regulate microglial motility. After local damage, the release of ATP induces microgliosis and activated microglial cells migrate to the site of injury, proliferate, and phagocytose cells and cellular compartments. However, excessive activation of microglia could contribute to the progression of chronic neurodegenerative diseases, though the underlying mechanisms are still unclear. Microglia have the capacity to release a large number of substances that can be detrimental to the surrounding neurons, including glutamate, ATP, and reactive oxygen species. However, how altered neurotransmission following acute insults or chronic neurodegenerative conditions modulate microglial functions is still poorly understood. This review summarizes the relevant data regarding the role of neurotransmitter receptors in microglial physiology and pathology.